Development of a multi-view fringe projection system for coordinate metrology - Shaheen, Amrozia (2021)
The aim of the thesis is the development of a novel methodology for the characterisation of a multi-view fringe projection system, comparing the developed methodology with the conventional approach, and performing the verification tests on the multi-view fringe projection system. In general, commercially available single-view fringe projection systems struggle to acquire the full form/shape in one acquisition due to multiple occlusions, complex freeform geometries, limited field of view and the line of sight issues. Multi-view fringe projection systems are considered an effective solution to overcome the limitations of existing single-view optical systems. However, characterisation of a multi-view system is challenging due to the complexity involved, the need for defining a global coordinate system for multiple cameras and projectors and the fusion of the data from multiple perspectives.